2009
DOI: 10.1038/ni.1763
|View full text |Cite
|
Sign up to set email alerts
|

Essential function for SAP family adaptors in the surveillance of hematopoietic cells by natural killer cells

Abstract: The adaptors SAP, EAT-2 and ERT are specific to cells of the immune system and belong to the SAP family. All three are expressed in natural killer (NK) cells. Here we examined the global function of the SAP family using mice lacking SAP, EAT-2 and ERT. These adaptors acted together in a mechanism that was essential for the elimination of hematopoietic but not nonhematopoietic cells by NK cells. This function was mediated by many receptors of the SLAM family on NK cells that were engaged by ligands found solely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
197
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(208 citation statements)
references
References 48 publications
10
197
1
Order By: Relevance
“…According to our observation, in SAP −/− mice, members of the SLAM receptor family have been shown to inhibit NKG2D that, different to humans, associates with both DAP10 and DAP12 [45,46].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…According to our observation, in SAP −/− mice, members of the SLAM receptor family have been shown to inhibit NKG2D that, different to humans, associates with both DAP10 and DAP12 [45,46].…”
Section: Discussionmentioning
confidence: 71%
“…44: 1526-1534 Innate immunity 1531 activation, a crucial effector of 2B4-mediated inhibition is represented by SHIP-1 (and possibly SHIP-2), which negatively regulates downstream signals such as PLC-γ-mediated Ca 2+ fluxes [14,43]. According to our observation, in SAP −/− mice, members of the SLAM receptor family have been shown to inhibit NKG2D that, different to humans, associates with both DAP10 and DAP12 [45,46].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, our results clearly identify that Ly49 ITIM signaling is required for NK-cell licensing, which highlights the need to better characterize the signaling pathways downstream of the Ly49 ITIM to differentiate between the arming and disarming hypotheses. Moreover, it will be important to investigate whether context can influence ITIM signaling similar to how the immunoreceptor tyrosine-based switch motif of SLAM family receptors can signal through distinct pathways to activate or inhibit NK cells depending on the setting (37). A previous study showed that NK cells from NKC KD mice express reduced levels of Ly49s due to concatemer insertion in the NKC, which leads to impaired killing of MHC-I-deficient splenocytes and tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…On NK cells, CD319 and CD229 act as coactivating receptors, which results in increased cytotoxicity against targets cells expressing CD319 and CD229 (35,36), whereas, on B cells, ligation of CD319 induces proliferation and cytokine production (37). In contrast, no study of the function of SLAM receptors on pDCs has been reported.…”
Section: Altered Expression Of Cd319 and Cd229 On Pdcs And Nk Cells Fmentioning
confidence: 99%